2022
DOI: 10.1177/0734371x221106792
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Work Engagement in the Public Sector: A Systematic Literature Review

Abstract: This article systematically reviewed the body of literature concerning work engagement in public organizations, aiming to examine the antecedents of work engagement in the public sector. Web of Science and Scopus, two prominent journal databases, were utilized to identify relevant literature. Adopting the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach, a final of 48 articles were systematically analyzed as research samples. The review identified five main themes: organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 64 publications
0
43
1
4
Order By: Relevance
“…Nine independent variables are included in the analysis: Effective Leadership: Empowerment, Effective Leadership: Senior Leaders, Effective Leadership: Supervisors, Employee Skills-Mission Match, Pay, Teamwork, Innovation, Work-Life Balance, and Recognition. These varaibles have been theorized to be antecedents of work enagement and satisfaction (Zahari & Kaliannan, 2022). The independent variables are based on one or more questions from OPM's FEVS.…”
Section: Datamentioning
confidence: 99%
“…Nine independent variables are included in the analysis: Effective Leadership: Empowerment, Effective Leadership: Senior Leaders, Effective Leadership: Supervisors, Employee Skills-Mission Match, Pay, Teamwork, Innovation, Work-Life Balance, and Recognition. These varaibles have been theorized to be antecedents of work enagement and satisfaction (Zahari & Kaliannan, 2022). The independent variables are based on one or more questions from OPM's FEVS.…”
Section: Datamentioning
confidence: 99%
“…As an important characteristic of organizations, the work practice environment plays a crucial role in creating employee-organizational relationships. When organizations provide a supportive environment (e.g., learning opportunities, cooperative interactions, and emotional support), a positive employee-organizational relationship is established, and employees' basic psychological needs are more likely to be fulfilled, which in turn promotes their engagement in work (7). Organizational commitment is a well-studied concept reflecting the employee-organizational relationship, which refers to one's feelings of attachment toward a particular organization (19).…”
Section: Introductionmentioning
confidence: 99%
“…To develop effective strategies that foster work engagement, identifying potential predictors of work engagement is imperative. Previous studies have shown that the antecedents of work engagement are diverse ( 6 , 7 ). For example, Zahari et al ( 7 ) summarized 48 articles related to work engagement and found that the predictors of work engagement could be divided into five categories, namely, organizational and team factors, perceived leadership, organizational intervention, job-related experience, and individual factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations